Technological issues of manufacturing critical castings for the nuclear industry from ferritic cast iron with spherical graphite - A. N. Poddubny (Литьë и металлургия)
The article describes technological solutions for casting blanks for containers for transportation of nuclear waste. As examples, calculations of external refrigerators are proposed to solve the issues of directional crystallization of the casting. Calculation of optimization of shrinkage processes is given. Specifically, the actual example shows a picture of the effect of shrinkage during the casting and cooling of the workpiece on the quality and density of the resulting casting material.